Potential Applications of Remote Limb Ischemic Conditioning for Chronic Cerebral Circulation Insufficiency - You, Jiulin; Feng, Liangshu; Bao, Liyang; Xin, Meiying; Ma, Di; Feng, Jiachun (Frontiers in Neurology, 2019)
Chronic cerebral circulation insufficiency (CCCI) refers to a chronic decrease in cerebral blood perfusion, which may lead to cognitive impairment, psychiatric disorders such as depression, and acute ischemic stroke. Remote limb ischemic conditioning (RLIC), in which the limbs are subjected to a series of transient ischemic attacks, can activate multiple endogenous protective mechanisms to attenuate fatal ischemic injury to distant organs due to acute ischemia, such as ischemic stroke. Recent studies have also reported that RLIC can alleviate dysfunction in distant organs caused by chronic, non-fatal reductions in blood supply (e.g., CCCI). Indeed, research has indicated that RLIC may exert neuroprotective effects against CCCI through a variety of potential mechanisms, including attenuated glutamate excitotoxicity, improved endothelial function, increased cerebral blood flow, regulation of autophagy and immune responses, suppression of apoptosis, the production of protective humoral factors, and attenuated accumulation of amyloid-β. Verification of these findings is necessary to improve prognosis and reduce the incidence of acute ischemic stroke/cognitive impairment in patients with CCCI.